KAJIAN SOSIOKULTURAL USAHA GARAM RAKYAT DI ACEH - Rochwulaningsih, Yety (HUMANIKA, 2013)
ABSTRACT The article entitled "Sociocultural Studies on People’s Salt Business in Aceh" examines the question of how people’s salt business in Aceh lasted for generations. How and why women seemed to play a bigger role in people’s salt business in Aceh and whether or not there were socio-cultural and economic dimensions underlying it. In-depth interview, focus group discussion, and observation data collection methods as well as documents and literature studies were used to examine the issue along with qualitative analysis methods. The findings showed that the salt-making business in Aceh was identical with women. In some areas such as East Aceh, North Aceh and Pidie, majority of salt-making business applied the boiling method although some areas also applied solar evaporation method. The dominance of boiling method implementation was able to construct the system of production relation pattern, distribution and marketing of people’s salt that placed women as the central figure. In this case, it was women that virtually dominated all stages in the complex process of making and marketing of salt, in the heat of the sun and the boiling kitchen, consuming a lot of power (energy) and time. The dominance implied the economical authority of women in their domestic life. Keywords: people's salt, boiling, solar evaporation, subsistence, valvular rescuer.